Sedentary behaviour levels in adults with an intellectual disability: a systematic review protocol - Lynch, Louise Annmarie (My University, 2020)
Background: Sedentary behaviour contributes to non-communicable diseases, which account for almost 71% of world deaths. Of these, cardiovascular disease is one of the largest causes of preventable death. It is not yet fully understood what level of sedentary behaviour is safe. People with an intellectual disability have poorer health than the general population with higher rates of multi-morbidity, obesity and inactivity. There is a paucity of evidence on whether this poorer health is due to sedentary behaviour or physical inactivity. This systematic review will investigate the sedentary behaviour levels of adults with an intellectual disability. Method: The PRISMA-P framework will be applied to achieve high-quality articles. An extensive search will be conducted in Medline, Embase, psycINFO and Cinahl and grey literature sources. All articles will be independently reviewed by two reviewers and a third to resolve disputes. Initially, the articles will be reviewed by title and abstract and then the full article will be reviewed using stringent inclusion criteria. All article data will be summarised in a standardised tabular format. The National Institute of Health’s quality assessment tool will be used to assess article quality. GRADE will be used to assess the quality of the evidence. The primary outcome of interest is the prevalence of sedentary behaviour levels for people with an intellectual disability. The definition of sedentary behaviour to be used for the purposes of this study is: ‘low physical activity as identified by metabolic equivalent (MET) or step levels or as measured by the Rapid Assessment of Physical activity questionnaire (RAPA) or the International Physical Activity questionnaire (IPAQ) or sitting for more than 3 hours per day’. Conclusion: This systematic review will provide a critical insight into the prevalence of sedentary behaviour in adults with an intellectual disability.
Keywords: Intellectual disability; Sedentary behaviour; Adults; Ageing; Intellectual Disability